Bienestar Físico y Psicológico Del Grupo De Adultos Mayores Del Barrio 20 De Julio: Un Enfoque Resiliente (2017)
In this research, an analysis is made of the resilient characteristics of older adults in the 20 de Julio neighborhood, based on the physical and psychological well-being to which they respond based on their life experience. Taking into account the above, a qualitative investigation is proposed, which is defined by Hernández (2014) as that detailed investigation that fulfills the function of seeking information with the objective of obtaining a detailed observation close to the facts, seeking the specific and local of what is not immediately observable, this type of research collects information carefully, from slow, prolonged and systematic observation that is collected from notes or recordings, in order to establish a permanent conversation between those who observes and what is being observed.